Role of Dalit Civil Society Against Untouchability: Challenges and Prospects - Lamsal, Hem Bahadur (New Angle: Nepal Journal of Social Science and Public Policy, 2012)
The paper is based on literature review complemented by interviews with Dalit civil society activists. After an introduction to the plight of Dalit communities in Nepal, the paper outlines the emergence of a Dalit civil society, the roles it has played and continues to play in national life, its achievements and the challenges Dalit associations have faced in the course of their work. The final section explores the prospects for Nepal’s Dalit civil society.